Studi Kelayakan Bisnis Pangkas Bintang Lima Ditinjau dari Aspek Makroekonomi, SWOT, dan Pemasaran - Apriani Hutabarat; Rejosu Vanhot Sianturi; Putri Kemala Dewi Lubis; Irma Siagian; Emia Perangin angin (Peneliti.net, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the service sector, particularly barbershops, play a strategic role in the local economy. This study aims to analyze the feasibility of the Pangkas Bintang Lima barbershop business from the perspectives of macroeconomics, SWOT analysis, and marketing strategies. The method used is a descriptive qualitative approach through observation, in-depth interviews, and documentation study. The results show that this business has a strategic location, low operational costs, and high customer loyalty. However, weaknesses are found in the aspect of legality (lack of official business permit) and the suboptimal use of digital technology. Development opportunities are wide open due to routine demand and the potential for service diversification, while the main threat comes from competition with modern barbershops. Overall, this business is considered feasible to operate, provided that legal strengthening and the adoption of digital marketing technologies are prioritized.